Pemanfaatan Digitalisasi dalam Pengembangan Wisata Arum Jeram untuk Mendukung Ekonomi Kreatif Islami di Desa Buluh Duri - Chairun Nissa; Delia Torsa Purba; Miranda Panjaitan; Sabrina Faranditha; Adlin Budhiawan (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
This study discusses the utilization of digitalization in developing rafting tourism in Buluh Duri Village as an effort to strengthen the Islamic creative economy. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that digitalization plays a vital role in tourism promotion through social media, websites, and online reservations, as well as improving services through the integration of sharia-based payment systems. Moreover, digitalization supports the empowerment of local MSMEs in halal culinary, handicrafts, and sharia-compliant homestays. Despite challenges such as limited digital literacy, inadequate internet infrastructure, and the absence of consistent marketing strategies, the application of digitalization has proven effective in expanding market reach, strengthening Islamic identity, and creating a competitive tourism ecosystem. With the right strategy, Buluh Duri Village has the potential to grow as a leading Islamic tourism destination that contributes to the development of a sustainable creative economy.